The assessment of anterior segment parameters using the Sirius topography in adults with anisohypermetropic amblyopia - Karaman Erdur, Sevil; Dikkaya, Funda; Demirci, Göktuğ; Özsütçü, Mustafa; Aydın, Rukiye; Eliaçık, Mustafa; Kocabora, Mehmet Selim (My University, 2018)
Aim: To evaluate anterior segment parameters in the eyes of adults with anisohypermetropic amblyopia using the Sirius topography device. Materials and Methods: Forty-eight patients with anisohypermetropic amblyopia were prospectively evaluated along with a control group of 45 healthy patients. All patients were examined with the Sirius topography system under cycloplegic and non-cycloplegic conditions. The anterior and posterior mean keratometry values, central corneal thickness (CCT), anterior chamber depth (ACD), corneal volume (CV), and anterior chamber volume (ACV) measurements were compared among groups. Results: No significant difference was found in the anterior and posterior mean keratometry values, CCT, ACD, CV, and ACV measurements between amblyopic, fellow, and control eyes under cycloplegic and non-cycloplegic conditions (p>0.05). Conclusion: This study shows that the anterior segment parameters measured by the Sirius topography device among amblyopic, fellow, and control eyes do not differ under both cycloplegic and non-cycloplegic conditions.

Amaç: Anizohipermetropik ambliyopisi olan yetişkinlerde ön segment parametrelerini Sirius topografi ile değerlendirmek. Gereç ve Yöntem: Anizohipermetropik ambliyopisi olan 48 hasta ve 45 sağlıklı yetişkin çalışma kapsamında prospektif olarak değerlendirildi. Tüm hastaların sikloplejik damla öncesi ve sonrasında Sirius topografi cihazı ile muayeneleri gerçekleştirildi. Ön ve arka ortalama keratometri değerleri, santral kornea kalınlıkları (SKK), ön kamara derinlikleri (ÖKD), kornea volümü (KV) ve ön kamara volümleri (ÖKV) gruplar arasında karşılaştırıldı. Bulgular: Ön ve arka ortalama keratometri değerleri, SKK, ÖKD, KV ve ÖKV arasında ambliyopisi olan hastanın ambliyopik gözü, diğer göz ve kontrol hastasının gözleri arasında sikloplejik damla öncesi ve sonrası ölçümlerde fark saptanmadı (p>0.05). Sonuç: Ambliyopisi olan yetişkinlerde ambliyopik göz, diğer göz ve kontrol gözler arasında sikloplejik damla öncesi ve sonrasında Sirius topografi ile yapılan değerlendirmede ön segment parametreleri arasında anlamlı fark saptanmamıştır.
Anizohipermetropik ambliyopisi olan yetişkinlerin ön segment parametrelerinin Sirius topografi ile değerlendirilmesi
Keywords: Anisometropic Amblyopia; Anterior Eye Segment; Corneal Topography; Anizometropik Ambliyopi; Ön Göz Segmenti; Kornea Topografisi